Buddhism and Gender: Reframing and Refocusing the Debate - Collett, Alice (Journal of feminist studies in religion, 2006)
, Within the Buddhism and gender debate in Western scholarship, various approaches to the study of Buddhist literature—Orientalist, Protestant Buddhism, and a doctrinal approach—have led to a taxonomy of value being accorded various texts such that some are overvalued and others either wholly or largely ignored. The first women scholars of Buddhist studies in the West—Caroline Rhys Davids, Mabel Bode, and I. B. Horner—labored under the Orientalist fallacy and thus set up some initial distortions in the survey of the textual record that have persisted. However, the work of these women also possesses many strengths and contemporary scholars would do well to follow their lead in continuing more detailed textual work in the field while also rescinding their overemphasis on the Pali literature and bringing into the frame all relevant texts by, about, or concerning women from ancient Indian Buddhism.